Penguatan Mitigasi Bencana: Membangun Kapasitas Sosial Masyarakat Melalui Peran Pelajar (Studi Kasus Bencana Banjir Kelurahan Campang Raya, Kecamatan Sukabumi, Kota Bandar Lampung) - Sya’bandi, M. Ismal; Afiani, Meidia; Puspa Rengganis, Audy Citra; Putri Celosia, Nabila; Prihantika, Ita (Fakultas Ilmu Sosial dan ilmu Politik, 2024)
Kelurahan Campang Raya, Kecamatan Sukabumi, Kota Bandar Lampung is one of the areas prone to flood disasters. This is due to the geographical location of Kelurahan Campang Raya, which is traversed by the flow of rivers from other neighborhoods with a fairly wide river. The river in this neighborhood often overflows, especially during the rainy season. Unfortunately, the residents of Kelurahan Campang Raya do not have adequate awareness regarding disaster mitigation actions and response efforts. This activity aims to provide education to the residents of Kelurahan Campang Raya, through the role of students from SMP N 31 Bandar Lampung. It is hoped that these students can become agents of change for their respective families. Using data collection techniques through pre-test and post-test questionnaires, we conducted a study with a total population of 150 students, and a sample size calculation of 10% of the population, thus the research involved 15 students as samples. Furthermore, the results of the pre-test and post-test were analyzed using the gain formula with gain criteria indicators to determine the improvement. Based on the analysis results, it indicates success in improving students' knowledge regarding disaster mitigation with more than half of the students from SMP N 31 Bandar Lampung. Keywords: students, capacity building, disaster mitigation.